(untitled) (Research, Society and Development, 2021)
This work addresses the use of the “Interactive Physics” application that can be installed on smartphones that use the Android system, and in addition, it can be used as a teaching tool for Physics in the classroom. Thus, this research aimed to analyze the use of the “Interactive Physics” application as a methodological resource in the teaching of Physics, as well as to identify whether smartphones can assist in the teaching-learning process, increasing the concentration on the studied contents. The qualitative research, made use of the case study with quantitative and qualitative data, considering as instruments of data collection, the observation and the application of interviews with closed questions. The investigation was carried out specifically in a class of first year of high school in a public school located in Bragança-PA. This study was applied in two phases, the first consisting of a small class with correction of questions extracted from the textbook, and the second consisting of using questions similar to the first phase where students had the help of the “Interactive Physics” application. Subsequently, the data were analyzed, indicating that the “Interactive Physics” application helps in the teaching and learning process of teaching Physics in public schools in Pará. The results allow us to point out that the use of the application in the classroom in the teaching of Physics dramatically alters the level of resolution of activities by the students. resolution of activities by students. And, in the same way, it demonstrates that the easiness and the improvement of the teaching and learning process is largely impacted by the use of the application in the act of solving the questions, indicating greater stimulus in learning, dynamism in the process and significance of the contents.